Effect of Complementary Therapy Combination of Progressive Muscle Relaxation and Music Therapy (RESIK) to Lower Blood Pressure in the Elderly - Nita Yulinda; Lita Heni Kusumawardani (UIMA Press, 2023)
Backgrounds: Hypertension is a disease that affects many elderly people. One effort that can be done to treat hypertension is to provide a combination therapy of progressive muscle relaxation and music therapy (RESIK). Objectives: The purpose of this study was to analyze the effect of RESIK therapy on clients with hypertension. Methods: The type of research used is a case study with a total sample of 3 respondents. The implementation of this study began with a pre test (measurement of blood pressure before being given RESIK therapy). Then give RESIK therapy 2x a day for 6 days with a duration of 25-30 minutes. After 6 days, blood pressure was measured again as post test data. Research data were analyzed using the Wilcoxon test. Results: Research results withWilcoxon test obtained sig. (2-tailed) has a value of 0.002 where the value is 0.002 <0.05 so it can be concluded that there is a significant effect of the combination therapy of progressive muscle relaxation and music therapy (RESIK) on blood pressure in the elderly. Conclusion: The results of this study indicate that there is a significant effect of RESIK therapy on reducing blood pressure in the elderly. Elderly people with hypertension are expected to carry out this RESIK therapy intervention independently, practically, efficiently and serve as an alternative complementary therapy to reduce blood pressure.